2009
DOI: 10.1001/archfacial.2009.46
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of Outcomes and Complications of 300 Consecutive Microvascular Reconstructions

Abstract: Previous radiation therapy and surgery are positive predictors for wound complications after microvascular reconstruction. Diabetes may add further risk in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 17 publications
5
53
0
Order By: Relevance
“…Microvascular free tissue transfer is widely used for the reconstruction of head and neck defects, with excellent overall success rates reported in large series 1–4. Complex defects can be addressed in a single stage, and functional and cosmetic outcomes optimized with free flap reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Microvascular free tissue transfer is widely used for the reconstruction of head and neck defects, with excellent overall success rates reported in large series 1–4. Complex defects can be addressed in a single stage, and functional and cosmetic outcomes optimized with free flap reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…42 Vessel thrombosis accounts for the majority of failures during the immediate postoperative period. Venous thrombosis is most common, accounting for 50% of flap failures.…”
Section: Flap Failurementioning
confidence: 99%
“…Although the method was initially met with some hesitation owing to concerns regarding their perceived dependability, subsequent studies [1][2][3][4][5][6] have confirmed the unparalleled reliability and versatility of free flaps as a reconstructive technique. Reconstruction of defects following oncologic resection of head and neck cancer is one of the most common indications for free flap surgery.…”
Section: Commentmentioning
confidence: 99%
“…Given the high reliability of free flaps for the head and neck, [1][2][3][4][5][6] this raises the question as to whether patients with peripheral vascular disease are a subset with potentially diminished free flap reliability. To the contrary of many earlier publications, in the current study, the incidence and pattern of postoperative complications and the risk of partial or total flap necrosis in patients with calcified atherosclerosis of the flap vascular pedicle was found to be similar to that which our group previously reported in 400 consecutive patients who underwent microvascular flap reconstruction of the head and neck.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation